Maging akin ka lamang - De Leon, Christopher; Tolentino, Lorna; Bonnevie, Dina; Ilagan, Jay; Dalisay, Jose; Salvador, Ramon; Brocka, Lino (Viva Films, 1986)
Rosita is obsessed with Andy and has tried to prevent him from marrying Elsa. When she is unable to do that, she steals their baby, hoping to break up their marriage, and brings him up as her own.